PLEONASME DALAM BERITA UTAMA TRIBUN PEKANBARU - Meilani Naina Sa’diah; Hasnah Faizah AR; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This type of research is descriptive. The object of this study is redundancy. The data source is the object of this study is redundancy words contained in the sentence Tribun headlines Pekanbaru. To obtain the data of the study authors do engineering documentation data relating to redundancy in the headlines Tribun Pekanbaru. The results of this study are as follows. (1) The use of the two words synonymous redundancy in the headline of the Tribun Pekanbaru is a form of redundancy which uses two types of words that have the same meaning in a way at once; (2) The use of excessive redundancy next word in the headline of the Tribun Pekanbaru is a form of redundancy that is the preposition that really should not be used; (3) The use of redundancy word with each other again in the form of headlines Tribun Pekanbaru is a form redundancy are on the meaning a two sides; (4) The use of redundancy concord or agreement in the headline of the Tribun Pekanbaru is a form of redundancy which uses plural meaningful words in a way at once; (5) Redundancy repeat the word in the headline of the Tribune Pekanbaru is a form of redundancy which uses the same word in one sentence or a repetition of the same word for the next sentence that has been used in the previous sentence. Redundancy dominating headlines Tribun Pekanbaru is the use of two words synonymous redundancy and concord or agreemet.Key Words: redundancy, headlines